A high-affinity subtype-selective fluorescent probe for estrogen receptor β imaging in living cells. Issue 31 (3rd April 2018) - Hu, Zhiye; Yang, Lu; Ning, Wentao; Tang, Chu; Meng, Qiuyu; Zheng, Jie; Dong, Chune; Zhou, Hai-Bing
Abstract : Distinct ERβ dynamics in various cellular bio-settings were directly visualized for the first time via fluorescent probeFPNM staining. Abstract : Estrogen receptor β (ERβ) has recently been identified as a pharmaceutical target in hormone replacement therapy for breast cancers. However, the biological function of ERβ in disease progression remains unclear. A highly ERβ-selective fluorescent probe (FPNM ) was discovered exhibiting nanomolar affinity for ERβ with an ERβ/ERα selectivity as high as 80, which allowed specific labeling of intracellular ERβ. Moreover, distinct ERβ dynamics in various cellular bio-settings such as prostate cancer (DU-145) or triple-negative breast cancer (MDA-MB-231) cells were directly observed for the first time via FPNM staining.